Pengembangan Usaha Produk Sosis Dengan Teknologi Sederhana Pada UMKM Kota Padang Panjang - Pelita, Elda; Suciati, Dwimaryam; Anwar, Hazil; Nirmala, Dyah; Youfa, Rita; Desniorita, Desniorita; Jayanti, Regna Tri; Permadani, Resi Levi; Sahaq, Anang Baharuddin (Journal of Industrial Community Empowerment, 2025)
Several MSMEs in Padang Panjang City are engaged in livestock and processed meat and poultry products. These MSMEs can still be said to be small businesses because they implement a pre-order (PO) system for marketing, the variety of products offered is quite diverse, but limited knowledge about quality meat processing and market demands related to food products that comply with halal principles, and effective marketing strategies are not yet well understood as seen from the product packaging which still looks simple. The purpose of this community service activity is for MSMEs to be able to develop and improve product quality, increase competitiveness in the market, and contribute to local economic growth. The ATI Padang Polytechnic Team provided assistance including the introduction of meat processing techniques to create new product variations such as good and halal sausages, selection of quality raw materials, and the right marketing strategies to increase product competitiveness. The activity was carried out on August 20, 2024. The results of the Community Service activities were shown from the questionnaire given to participants. It is known that MSMEs in Padang Panjang city have been able to understand about natural and artificial food additives, healthy and halal meat processing processes, halal certification, shelf life of processed meat products and effective marketing methods.